Can the State Administrative Court Shield Citizens from Government 'Tort'? A Path to Justice in Dispute Resolution - Widianta, RM Ivansyah Gusti; Akbarsyah, Iqbal Salamuddin (Indonesian State Law Review, 2024)
In democratic governance, protecting citizens from wrongful acts by the government is crucial to maintaining public trust and ensuring justice. In Indonesia, the State Administrative Court (PTUN) serves as the primary forum for resolving disputes between individuals or legal entities and government authorities. However, when these disputes involve acts of "government tort"—illegal or wrongful actions by the state—citizens often face significant challenges in seeking redress. This research explores the role of the PTUN in protecting citizens against government torts, focusing on its capacity to provide timely and effective remedies. Using a normative juridical approach, this study analyzes the current legal framework and procedural mechanisms within the PTUN, highlighting the barriers citizens face when challenging government actions. The findings reveal that while the PTUN offers a critical platform for redress, its effectiveness is hindered by procedural complexities, limited legal remedies, and slow judicial processes. The research argues that reforms are urgently needed to enhance the PTUN’s role as a protector of citizens' rights in the face of government torts. This research introduces the novel concept of "government tort" within the context of Indonesia's administrative justice system, offering fresh insights into its application in legal practice. The urgency of reform lies in ensuring that citizens can effectively challenge government actions that harm their rights and freedoms. The study’s contribution is significant in providing recommendations for legal and procedural reforms aimed at strengthening the PTUN, ensuring that it can offer timely and accessible remedies for individuals harmed by government misconduct.